A dual-mode hemispherical sparse array for 3D passive acoustic mapping and skull localization within a clinical MRI guided focused ultrasound device. (15th March 2018) - Crake, Calum; Brinker, Spencer T; Coviello, Christian M; Livingstone, Margaret S; McDannold, Nathan J
Abstract: Previous work has demonstrated that passive acoustic imaging may be used alongside MRI for monitoring of focused ultrasound therapy. However, past implementations have generally made use of either linear arrays originally designed for diagnostic imaging or custom narrowband arrays specific to in-house therapeutic transducer designs, neither of which is fully compatible with clinical MR-guided focused ultrasound (MRgFUS) devices. Here we have designed an array which is suitable for use within an FDA-approved MR-guided transcranial focused ultrasound device, within the bore of a 3 Tesla clinical MRI scanner. The array is constructed from 5  ×  0.4 mm piezoceramic disc elements arranged in pseudorandom fashion on a low-profile laser-cut acrylic frame designed to fit between the therapeutic elements of a 230 kHz InSightec ExAblate 4000 transducer. By exploiting thickness and radial resonance modes of the piezo discs the array is capable of both B-mode imaging at 5 MHz for skull localization, as well as passive reception at the second harmonic of the therapy array for detection of cavitation and 3D passive acoustic imaging. In active mode, the array was able to perform B-mode imaging of a human skull, showing the outer skull surface with good qualitative agreement with MR imaging. Extension to 3D showed the array was able to locate the skull within  ±2 mm/2° of reference points derived from MRI, which could potentially allow registration of a patient to the therapy system without the expense of real-time MRI. In passive mode, the array was able to resolve a point source in 3D within a  ±10 mm region about each axis from the focus, detect cavitation (SNR ~ 12 dB) at burst lengths from 10 cycles to continuous wave, and produce 3D acoustic maps in a flow phantom. Finally, the array was used to detect and map cavitation associated with microbubble activity in the brain in nonhuman primates.